Anticancer Evaluation of Plants from Indonesian Tropical Rain Forests - Abbas, Jamilah (Indonesian Journal of Cancer Chemoprevention, 2011)
The Â anticancer Â activities Â of Â medicinal Â plants Â from Indonesiaâs tropical rainforests wereÂ investigated Â against Â Hela Â cell Â line. Â Maytenfoliol Â from Â leaves Â of Â Calophyllumtetrapterum Â 3-epibetulinic Â acid Â from Â stem Â bark Â of Â  Â C. Â tomentosum Wight Â and Â D.A-friedo-oleanan-3-on Â fromÂ stem bark of C. moonii showed anticancer activity. The compound 3-epibetulinic acid showed theÂ more potent anticancer activity than maytenfoliol Â and D.A-friedo-oleanan-3- with thean IC50 Â value were 3.17 Î¼g/mL, 4.89 Î¼g/mL and 5.63 Î¼g/mL, respectively.Keywords: Anticancer Â evaluation, Â Hela Â cell Â line, Calophyllumtetrapterum. Â C. Â tomentosum WightÂ and Â C. moonii